2015
DOI: 10.1038/cdd.2015.87
|View full text |Cite
|
Sign up to set email alerts
|

MAP3K11 is a tumor suppressor targeted by the oncomiR miR-125b in early B cells

Abstract: 5These authors contributed equally to this work.Received 20.11.14; revised 05.5.15; accepted 22.5.15; Edited by G Melino; published online 03.7.15Abbreviations: Abtb1, ankyrin repeat and BTB (POZ) domain containing 1; ALL, acute lymphoblastic leukemia; Arid3a, AT-rich interactive domain-containing protein 3A; Bak1, BCL2-antagonist/killer 1; Bbc3, BCL2 binding component 3; BCR, B-cell receptor; Blzf1, basic leucine zipper nuclear factor 1; Bmf, Bcl2-modifying factor; BTK, Bruton's tyrosine kinase; CBFB, core-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…The pre-B cell lines 1676 and 74 have already been described [23,62]. The pre-B cell lines 1676 and 74 have already been described [23,62].…”
Section: Cells Cell Culture and Retroviral Transductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pre-B cell lines 1676 and 74 have already been described [23,62]. The pre-B cell lines 1676 and 74 have already been described [23,62].…”
Section: Cells Cell Culture and Retroviral Transductionmentioning
confidence: 99%
“…For the 3 0 -UTR assay, UTRs of interest were cloned by PCR and ligated into LMP-destGFP [62] 3 0 of the destabilized GFP cDNA via XhoI and ClaI. In short, overlapping forward and reverse PCR primers were designed based on the mature miRNA sequence, for example, CAAGACCTGTgatTCTACCTTCCGT and atcACAGGTCTTGACGGA AGGTAGA (lower cases mark the mismatch region, the linker between the binding sites in underlined) for miR-1839 (AAGGTAG ATAGAACAGGTCTTG).…”
Section: Plasmid Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings might be compatible with our data of PVR gene body methylation perhaps leading to gene transcription promotion in KA and SCC. On the other hand, Knackmuss et al reported that MAP3K11 protein might function as an important tumor suppressor neutralized by oncomiR-125b in B-cell leukemia [24], although the function of MAP3K11 in epidermal tumors is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] Several target genes have been identified and postulated to have a role in the oncogenic properties of overexpressed miR-125b, such as Trp53inp1 and MAP3K11, which facilitate cell survival. 8,12 A genetic deletion of the gene encoding IRF4 has also been reported in miR-125b dysregulationinduced B cells. 11 In addition to promoting leukemia, several in vitro studies also suggest a role for this microRNA in B-cell development and differentiation.…”
Section: Introductionmentioning
confidence: 99%